Analyzing Transformational Leadership Style and Work Motivation Towards Organizational Commitment with Job Satisfaction as an Intervening Variable at the Representatif Office of Bank Indonesia North Sumatra - Qori Aulia Harahap; Elfitra Desi (CV. Doki Course and Training, 2026)
This study aims to examine the effect of Transformational Leadership Style and Work Motivation on Organizational Commitment, with Job Satisfaction serving as an intervening variable at the Representative Office of Bank Indonesia Medan, North Sumatra. The research employs a quantitative approach using Structural Equation Modeling (SEM) through SmartPLS 3.0 software. The population consists of all employees at the office, and the sample was selected using a saturated sampling technique. Data were collected via questionnaires and analyzed using SmartPLS. The results reveal that Transformational Leadership Style significantly affects Job Satisfaction, but does not have a direct significant impact on Organizational Commitment. Work Motivation shows a significant influence on both Job Satisfaction and Organizational Commitment. In addition, Job Satisfaction significantly affects Organizational Commitment. The indirect effect analysis indicates that Job Satisfaction does not mediate the relationship between Transformational Leadership Style and Organizational Commitment, but it successfully mediates the effect of Work Motivation on Organizational Commitment. These findings highlight that improving employee motivation and job satisfaction is crucial for strengthening organizational commitment.